Pengaruh Model Discovery Learning terhadap Minat dan Hasil Belajar Siswa pada Materi Laju Reaksi - Paskaria Br Ketaren; Nora Susanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the effect of the discovery learning model on students' interest and learning outcomes regarding the topic of reaction rates. This research employed a quasi-experimental design with a two-group pretest-posttest approach. The study population consisted of all Grade XI students at SMA Swasta GBKP Kabanjahe; two classes an experimental class and a control class were selected as the sample using cluster random sampling. Research instruments included a learning outcome test and a learning interest questionnaire. Data analysis techniques comprised tests for normality, homogeneity, N-Gain, t-tests, and correlation analysis. The results showed N-Gain scores of 0.60 for the control class and 0.661 for the experimental class, indicating a significant effect of the discovery learning model on students' interest and learning outcomes. Thus, the discovery learning model proved effective in enhancing students' interest and learning outcomes regarding the topic of reaction rates.